SPP1 and CXCL9 Promote Non-alcoholic Steatohepatitis Progression Based on Bioinformatics Analysis and Experimental Studies - Wang, Wen; Liu, Xiaojing; Wei, Peiyao; Ye, Feng; Chen, Yunru; Shi, Lei; Zhang, Xi; Li, Jianzhou; Lin, Shumei; Yang, Xueliang (Frontiers in Medicine, 2022)
Non-alcoholic fatty liver disease (NAFLD) is a major chronic liver disease worldwide, and non-alcoholic steatohepatitis (NASH) is one of its pathological subtypes. The pathogenesis of NASH has not yet been fully elucidated. The purpose of this study was to identify the hub genes and pathway of NASH using bioinformatics methods. The hub genes were further confirmed in human and animal levels.Three Gene Expression Omnibus (GEO) databases GSE48452, GSE58979 and GSE151158 of NASH patients and healthy controls were included in the study. We used GEO2R to identify differentially expressed genes (DEGs) between NASH patients and healthy controls. Functional enrichment analyses were performed to explore the potential functions and pathways of DEGs. In all DEGs, only two genes were highly expressed of NASH patients in three databases, so these two genes will be further studied. Serum and liver tissues from NASH patients and healthy controls were collected. The contents of serum ALT and AST were determined in NASH patients and healthy controls. Liver tissues were stained with hematoxylin-eosin (H&E). Immunohistochemical staining was used to evaluate the expression levels of the two genes in liver tissues. Male C57BL/6J mice were fed MCD diet for 8 weeks, serum ALT and AST levels were detected, while liver tissues were stained with H&E and immunohistochemistry with SPP1 and CXCL9 in mice. SPP1 and CXCL9 were the hub genes in three databases. “Lipid metabolism” “Inflammatory response” and “lymphocyte activation” were the most significant biological functions in GSE48452, GSE58979, and GSE151158 respectively. The KEGG pathway analysis showed that the toll-like receptor signaling pathway was significantly enriched. Serum ALT and AST were significantly increased in NASH patients than healthy controls. Liver tissues were more serious steatosis, hepatocyte ballooning degeneration and lobular inflammatory infiltration, and the expression of SPP1 and CXCL9 in liver cells were significantly upregulated in NASH patients compared with healthy controls. MCD diet mice were consistent with NASH patients. SPP1 and CXCL9 may play an important role in NASH’s pathogenesis, which could be the potential therapeutic targets and biomarkers of NASH in the future. More experimental studies are needed to confirm our results in the future.